Effect of loop diameter on the performance of MKR-based dual-wavelength erbium-doped fiber laser - Sulaiman, A.; Harun, Sulaiman Wadi; Norizan, S.F.; Dimyati, K.; Ahmad, Harith (John Wiley & Sons, 2013)
A dual-wavelength Erbium-doped fiber laser (EDFL) is demonstrated using a 1.5-m long EDF with a microfiber knot resonator (MKR) structure at the output end. The MKR is fabricated by heating and stretching a 3-cm long piece of EDF to form a microfiber, which is then manipulated to create a knot. The performance of the EDFL is investigated for two different MKR loop diameters. At a loop diameter of 4 mm, dual-wavelength laser is obtained at 1532.4 and 1556.0 nm with peak powers of −7.5 and −7.1 dBm and the corresponding optical signal-to-noise ratios of 22 and 32 dB, respectively. As the MKR diameter is reduced to 2 mm, the operating wavelength of laser shifts to a shorter wavelength, especially for the second lasing with a significant drop in output power due to the bending loss, which is more pronounced at smaller loop diameter. The slope efficiency of the EDFL drops from 0.55 to 0.09% as the MKR diameter decreases from 4 to 2 mm.